Development of chicken patties incorporated with onion (Allium cepa) and beet root (Beta vulgaris) extract powder - Nagre, Shubhangi S; Chappalwar, Anita M; Rindhe, Sandeep N; Londhe, Sanjay V; Nikam, Mahalsakant G (Journal of Meat Science, 2023)
Meat and meat products are dense source of nutrients, having health  and industrial importance. However nutrient rich meat and its products  have low stability even at low temperature. Application of natural  antioxidants to perishable food product for enhancing stability is an  innovative concept. Therefore the present study was planned to develop  chicken patties incorporated with different levels 0.75, 1.5 and 2.25% of  onion or beet root extract powder. From the study, it is observed that  the pH and cooking yield values were decreased significantly in onion  and beetroot extract treated patties respectively. Moisture, fat, protein  content decreased significantly (P
Keywords: Antioxidants; shelf life; chicken patties; onion extract powder; beetroot extract powder